Iniadi pearl millet germplasm as a valuable genetic resource for high grain iron and zinc densities. Issue 1 (15th May 2014) - Rai, K. N.; Velu, G.; Govindaraj, M.; Upadhyaya, H. D.; Rao, A. S.; Shivade, H.; Reddy, K. N.
Abstract : Crop biofortification is increasingly being recognized as a cost-effective and sustainable approach to address the widespread micronutrient malnutrition arising from Fe and Zn deficiencies. Pearl millet as a cereal crop species has higher Fe density than all other major cereals. Earlier studies in pearl millet have shown that breeding lines, hybrid parents, improved populations and composites having high Fe and Zn densities were often based largely or entirely on iniadi pearl millet germplasm. In an attempt to identify additional sources of high Fe density in this group of germplasm, 297 accessions were screened using Perl's Prussian Blue staining, of which 191 accessions (118 from Togo, 62 from Ghana and 11 from Burkina Faso) were re-evaluated during the 2010 rainy and 2012 summer seasons using the inductively coupled plasma atomic emission spectroscopy method. On the basis of the mean performance over the two seasons (environments), large variability was observed for both Fe (51–121 mg/kg) and Zn (46–87 mg/kg) densities. There was a highly significant and positive correlation between the two micronutrients ( r = 0.77, P < 0.01). Of these re-evaluated accessions, 49% had higher Fe density than the high-Fe control commercial cultivar ICTP 8203 (81 mg/kg), and most of these accessions also had Zn density ≥ 61 mg/kg (59 mg/kg for ICTP 8203). A total of 27 accessions (20 from Togo and seven from Ghana) having a Fe density of 95–121 mg/kg (1 standard error of difference above that for ICTP 8203) and a Zn density of 59–87 mg/kg were selected as a valuable germplasm resource for genetic improvement of these two micronutrients in pearl millet.